Balaghah Science and the Development of YouTube Learning Media - Mahmasoni, Muhammad Subhi (Muntaha Noor Institute, 2025)
This traditional and classical science is generally presented in book form, requiring considerable effort to carry, open, and especially read. Furthermore, it requires considerable effort to learn, from the basics of grammar and grammar to Balaghah. Therefore, the development of YouTube for Balaghah learning is worth experimenting with. It is hoped that this YouTube platform will enable students to practice language skills to the fullest. It is also hoped that this platform will pique students' interest due to its ease of access, viewing, reading, listening, and potential for easy memorization. This platform is designed to be used for in-depth learning with guidance from educators, as well as for independent learning such as murojaah. On the other hand, with this medium, learning principles and strategies will automatically flow smoothly.